Best Answer

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals" etc. Also use ^ to indicate powers (eg x-squared = x^2).

More answers

Assuming the missing signs are pluses, that factors to (2x + 3)(x + 3)

Q: How do you factor 2x2 9X 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Basic Math

The GCF is 9.

2x2 + 17x - 9 = 2x2 + 18x - x - 9 = 2x(x + 9) - 1(x + 9) = (2x - 1)(x + 9)

9(x - 3y)

(2x+3)(x+3)

factor out a 3x 3x(x-3)=3x2-9x

Related questions

2x2 - 9x = 18 2x2 - 9x -18 = 0 (2x - 18)(x + 9) x= -9 and 9

2x2 + 10 - 9x = 0 or 2x2 - 9x + 10 = 0 So (x - 2)*(2x - 5) = 0

2x2 - 9x + 4 = (2x - 1)(x - 4)

(2x + 1)(x + 4)

2x2+9x+9 = (2x+3)(x+3) when factored

2x2 - 9x + 10 = 2x2 - 4x - 5x + 10 = 2x(x - 2) - 5(x - 2) = (x - 2)(2x - 5)

2x2 + 10 = 9x 2x2 - 9x + 10 = 0 (x - 2)(2x - 5) = 0

I hope you mean x3+2x2-9x+18. Treat the equation like two equations: x3+2x2 and 9x+18. Factor out x2 from the first equation, so x2(x+2). Factor out 9 from the second equation, so 9(x+2). Now, the whole equation. x2(x+2)-9(x+2). Factor out (x+2), so (x+2)(x2-9). (x2-9) factors into (x+3)(x-3). So, (x+2)(x+3)(x-3) is the complete factorization. Hope this helps.

If you mean: 2x2 -9x +4 then it can be factored to (2x-1)(x-4)

x2-9x = x(x-9)

you can't

The factorisation is as follows: 2x2 + 7x - 9 = (x - 1)(2x + 9).